Corporate Reporting in the Modern Era - A Comparative Study of Indian and Chinese Companies - Shukla, Anita; Gekara, Mouni Geoffrey (Indian Journal of Finance, 2010)
One of the most rapidly growing areas of internet technology is the World Wide Web, which is used for business communication in various forms. It has the potential to be used in almost all the functional areas of management and business. Recently, the companies have started reporting their financial results and other information relating to the business on their website. The internet technology provides a new platform for disseminating all this information. It is a technology that has the potential to exhibit distinctive and attractive features of information which makes it an efficient and cost effective measure as compared to the traditional methods of printed media. It offers users the facilities to access documents containing multimedia mixtures of text, graphics, sound and video in a standard format which is open to everyone. It is a fast, cheap and increasingly used media of information in the business world today.